Assessment of Road Network Connectivity in Support of New Capital Development - . Junaidi; Sakti A. Adisasmita; Muhammad S. Pallu; M. Isran Ramli (Salehan Institute of Higher Education, 2022)
The shifting of the capital of Indonesia from Jakarta to East Kalimantan, or East Borneo, is underway. There are certain to be new issues that arise as a result of this migration. The state of the nation's current transportation infrastructure is one of the most prominent right now. The new capital of Indonesia, Jakarta, is situated in the midst of a jungle. For this reason, the road network should be established before, or at least concurrently with, the IKN construction. It is critical to understand the direction of future growth in the IKN region before developing a road network architecture. Potential partner locations might potentially benefit from enhanced access and connection to the existing road network in this situation as well. To ensure that the IKN is able to work properly and link additional nodes, many partner area points are being considered. A literature review, a focus group discussion, and in-depth interviews were conducted to come up with a development plan for IKN partner regions and highlight areas of special concern. It was also determined if the addition of a new node had a positive impact by utilizing a connection matrix and the accessibility index. Most linkages are found at five of the 26 nodes in the complete connectivity matrix of national highways around IKN in East Kalimantan. Node 3 and Node 7 are the most accessible and easy-to-access component nodes of the road network, compared to other nodes. Doi: 10.28991/CEJ-2022-08-10-011 Full Text: PDF